A Southern policing perspective and appreciative inquiry: an ethnography of policing in Vietnam - Jardine, Melissa (Policing and society, 2020)
Policing knowledge has been dominated by scholarship from the Global North, and largely Western, Anglo-American contexts. Whilst some aspects of Vietnamese society have been exposed to academic and international scrutiny in recent decades, policing norms and structures remain opaque. Exploring why this is the case requires interrogation of the intersections of policing, place and the production of policing knowledge. A Southern perspective on policing has dual aims: firstly, to highlight the dynamics which have hidden, limited or excluded some scholarship on policing, and secondly, to provide a framework to understand how police culture and socialisation occur in different structural environments. This article considers how insights from Appreciative Inquiry (AI) as a mode of inquiry can facilitate undertaking ethnographic research on policing in sensitive and complex political environments, particularly in the global South. It includes my personal reflections on navigating approval of the research, ethics and access to the field. The results of the overarching study found there are more variations in policing practices and cultures than some current assumptions allow because there are a wider range of structural conditions than reported in dominant literature. The research also contributes to scholarship that highlights how police ‘culture’ is not universally a pejorative term and argues that specifically invoking ‘culture’ can form part of an ethnographer’s toolkit. Overall, an ‘appreciative’ approach has potential to contribute to the democratisation of knowledge for a more comprehensive and inclusive account of policing and police culture.